"Evaluation of physico-mechanical properties of naturally dyed betel-nut leaf plate (BLPF) – Banana blended fabric". Issue 2 (February 2023) - Hassan, Mohammad Naim; Mondal, Moni Sankar; Hasan, Naimul; Reza, Md Masum; Rahman, Md Ishtiaque; Sarkar, Joy; Mohsin, Nourin; Hridoy, Rafat Mahmud; Jalal Uddin, Dr Ahmed
Abstract: Betel-nut leaf plate fiber (BLPF) is a lingo-cellulosic natural fiber that can be used to make eco-friendly and biodegradable blended or hybrid fabric with Banana fiber. In the world of organic textiles, naturally dyed BLPF-Banana fiber can be used for wearable products and satisfy health and hygiene issues. BLPF and Banana fiber can be good natural fibers for hybrid fabrics despite being considered waste materials. In this research work, both of the fibers were pretreated carefully to get the desired fineness, color, flexibilities, etc., which are necessary to manufacture fabric. BLPF-Banana woven (1 × 1) hybrid fabric was developed where 12 Ne Banana yarns were used in the warp direction, and 20 Ne BLPF yarns were used in the weft direction and it was dyed naturally with Turmeric. Evaluations of different physico-mechanical properties; tensile strength (854.9 N), tearing strength (14.5 N), stiffness (3.1 N), crease recovery (75° angle), and fabric thickness (1.33 mm) of naturally dyed BLPF-Banana blended fabric were tested, and found satisfactory. SEM, FTIR, and Water vapor transmission tests were also conducted in this study. It attempted to turn the wastages into an asset to make a unique biodegradable BLPF-Banana hybrid fabric by blending two types of natural fibers with the help of natural dyeing substance; it could be a god replacement for synthetic blended fabric.